Peran Sistem Reward dalam Pencapaian Kurikulum Pembelajaran Nahwu melalui Strategi Hafalan Alfiyah Ibnu Malik - Fika Al-Maghfiroh; Nida’ Muthmainnah; Dewi Aliyah Ibrahim; Avi Vera Afrinada (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Nahwu learning based on memorizing Alfiyah Ibnu Malik has long been used in Islamic boarding schools, but its effectiveness in supporting curriculum achievement still largely depends on the management system of students' learning motivation. One instrument that is widely used, yet has been minimally studied from a curriculum perspective, is the reward system. This study aims to analyze the role of the reward system in improving curriculum achievement in nahwu learning through the Alfiyah Ibnu Malik memorization strategy at Pondok Pesantren Putri Salafiyah 2 Bangil. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation involving students at the Madrasah Aliyah level. The results of the study indicate that the reward system, which is directly linked to memorization achievements through regular deposit mechanisms, scheduled revision, and final evaluations, functions as a reinforcement instrument that enhances students' discipline, diligence, and learning consistency. Formally and structurally provided rewards not only motivate students to achieve their memorization targets but also help the institution to control the achievement of the nahwu curriculum more systematically. These findings indicate that the reward system not only serves as external motivation but also functions as part of curriculum management that bridges cognitive goals (mastery of nahwu rules) and the development of students' learning character. This study contributes to the development of a nahwu learning model based on memorization, integrated with a motivation and curriculum management system in the pesantren environment.